Expansion of Residential Colonies and Conversion of Farmland in Bahawalpur City, Pakistan: A Temporal View - Muhammad Mohsin,; Muhammad Nasaru Minallah ,; Asad Ali Khan, (Journal of Basic & Applied Sciences, 2016)
This study focuses on the issue of farmland conversion into housing colonies in Bahawalpur City. In order to understand the magnitude of this issue, data of 102 sample colonies was collected for the period of 1950-2011 through field survey and secondary sources including TMA Bahawalpur City. The year of establishment, area occupied and legal status of colonies were recorded and the data were aggregated into 10-year categories for analysis and to produce temporal maps. Results indicate that during the last 61 years, an area of 1,142 acres (462.15 hectares) had been converted to 102 colonies at an average rate of 18.72 acres per year. Among these colonies only 18 were approved by concerned authorities whereas 84 were not approved legally. Approved colonies occupy an area of just 197 acres (17.25% of the total) whereas non-approved colonies and towns cover a huge area of 945 acres (82.74%). The conversion of farmland fluctuated substantially over time. During the period of 1950-1960 merely seven colonies were built which consumed an area of 97 acres indicating a conversion rate of 9.7 acres per year, while during the period of 2000-2010 a total of 32 colonies were built that consumed an area of 422 acres (170.77 hectares) indicating conversion rate of 42.2 acres per year. These findings indicate that the rate of farmland conversion is accelerating. If this trend goes unchecked, the problem of farmland conversion may change into a serious threat for future food supplies. This study identified several suggestions to tackle the issue.